Literary strategies and the legal representation in John Grisham’s The Firm (1991), A Time to Kill (1989) and The Chamber (1994) - Too, Gideon Kiplangat; Mwihia, Margaret Njoki; Mwangi, Peter Muhoro (Research Journal in Advanced Humanities, 2023)
This article analyzes various literary strategies that John Grisham has used to develop his legal issues in A Time to Kill, The Firm and The Chamber. The study aims to investigate how Grisham’s use of literary devices has helped him convey the relationship between society and the law. This is accomplished by an examination of the author’s literary choices, the tactics that highlight the relationship between the law and society, and the motivations behind the language used by the characters and, if any, the omniscient narrator. We can determine the communication levels of a text by examining both the overt and covert meanings of the language used. To effectively carry out this study, Structuralism was used as a theory for analysis. From the study, it is established that Grisham has utilized the structure of a legal thriller, a hard-boiled protagonist, legal jargon, double narration, and an omniscient narrator.